Structural Design in Wood - Stalnaker, Judith J. author. aut Link
XV, 426 p. 306 illus.
Keywords: Why another textbook on the design of wood sets this book apart is its inclusion of "struc structures? In many years of teaching structural tural planning. " Most textbooks show only the design in wood, the authors have used virtually selection of member proportions or number of every textbook available, as well as using only connectors in a joint to satisfy a given, com a code and no textbook at all. The textbooks pletely defined situation. This book, on the used have included both the old and the rela other hand, shows the thinking process needed tively modem; some have been fairly good, but to determine whether or not the member is re in our opinion each has deficiencies. Some quired in the first place. Following this, the books have too few solved examples. Others spacing and continuity of the member are de omit important material or have an arrange cided, its loads are determined, and finally its ment making them difficult to use as formal shape and size are selected. teaching tools. By writing this book, we intend We believe that illustrating structural plan to correct such deficiencies. ning as well as detailed member and connec The prime purpose of this book is to serve as tion design is of considerable value in helping a classroom text for the engineering or archi the student make the transition from the often tecture student.